Information management and the return-entry process: Examining information needs, sources, and strategies after Superstorm Sandy. (1st February 2021) - Manandhar, Rejina; Siebeneck, Laura K.
Abstract: The effective management of disasters requires timely and accurate information. Both emergency management (EM) organizations and the public are involved in information management activities during and after a disaster where they seek information from various sources to reduce disaster-related uncertainties. While studies have focused on information needs and source reliance behaviors of EM organizations amid a disaster, the information management behaviors of the organizations during return-entry phase has gained little scholarly attention. This study examines the information management strategies of local EM organizations while managing the initial return-entry movement following Superstorm Sandy. Using a qualitative research design, the researchers conducted semi-structured telephone interviews with 25 EM officials from New Jersey. The data analysis yielded five themes that highlight the information management strategies of the EM organizations – information needs, information sources, information seeking behavior, information exchange, and applying information for return-entry decisions. This paper discusses these findings and provides proactive strategies to gather and manage information to facilitate return-entry decision-making and risk communication in the immediate aftermath of a disaster.